(untitled) (Scientific journal of the Fergana State University, 2023)
The socio-philosophical foundations of the development of innovative ecological thinking are studied in this article. Also, the use of scientific conclusions in the implementation of traditions and innovations, social prudence, more attention to national traditions leads to bigotry and stagnation, more attention to innovations leads to instability, futurological assumptions and weakening of management. It is based on the existence of ethnogeographical factors among the socio-economic reasons that cause environmental problems during global development. Therefore, the main attention is focused on the research of the social aspects of the ecological culture of the ethnos, which is a result of living in the natural environment in which it was formed.